Evaluation of efficacy of four disinfectants on striated and non-striated orthodontic instruments: An in vitro study - Nagaraj Venkatachalam; Niveddha Ramesh; Prasanna Turuvekere; SM Vignesh Prasad; Mohamad Ramees; Chethan Kumar (Wolters Kluwer Medknow Publications, 2020)
Introduction: To achieve effective infection control only disinfecting instruments is not perfect when sterilization is an ideal method. Few chemical disinfection methods have disadvantage of not killing spores as cross infection is of great importance in dentistry; Standard sterilization and disinfection protocols must be followed by dental health care professionals for efficient infection control. Aim: The aim of this study was to evaluate the efficacy of undiluted concentrations of Durr Dental system, Bacillol, Savlon, and Dettol for disinfection of striated and nonstriated orthodontic instruments. Materials and Methods: Orthodontic instruments were divided into two groups. Each group of instrument was exposed to three microbes: Streptococcus mutans, Candida albicans, and Bacillus subtilis. Once the instruments were exposed to bacterium, they were immersed in four commercially available disinfectants: Durr Dental solution, Bacillol, Dettol, and Savlon. Culture streaks were taken at 5, 10, and 15 min of contact time and growth of organisms was observed on culture media. Results: All the four disinfectants showed no growth of bacteria and all were significantly effective. As per the immersion time factor, Durr system and Bacillol were more efficient than Dettol and Savlon. Conclusion: Study concluded that there was no growth of bacteria after disinfecting in all the four disinfectants. Dettol and Savlon were unable to eliminate B. subtilis at 5 min of contact time. All the disinfectants were effective in eliminating the microorganisms at 10 and 15 min postexposure.